2014
DOI: 10.1073/pnas.1407447111
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the immune-checkpoint VISTA gene imparts a proinflammatory phenotype with predisposition to the development of autoimmunity

Abstract: Significance The discovery of V domain-containing Ig suppressor of T-cell activation (VISTA) as a novel immune-checkpoint regulator comes at an exciting time, as the field of cancer immunotherapy has made significant progress owing to the clinical success of targeting immune-checkpoint proteins such as cytotoxic T lymphocyte-associated antigen 4 and programmed death 1 and ligand. Recent studies also show the promise of monoclonal antibody-mediated VISTA targeting for enhancing antitumor immunity in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
198
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 160 publications
(206 citation statements)
references
References 31 publications
8
198
0
Order By: Relevance
“…To address this question, mice were immunized with soluble antigenic peptides together with poly (I:C) (TLR3 agonist) as adjuvant. 2W1S, an MHC class II-restricted peptide, and OVA 257-264 , an MHC class I-restricted peptide, were used (22). On day +7 postimmunization, splenic T cells were isolated and restimulated ex vivo with the respective peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this question, mice were immunized with soluble antigenic peptides together with poly (I:C) (TLR3 agonist) as adjuvant. 2W1S, an MHC class II-restricted peptide, and OVA 257-264 , an MHC class I-restricted peptide, were used (22). On day +7 postimmunization, splenic T cells were isolated and restimulated ex vivo with the respective peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic disruption of VISTA accelerated autoimmune disease on a susceptible background, as well as resulted in multiorgan chronic inflammation because of spontaneous T-cell activation (22). Aged PD-1 KO mice were reported to develop late-onset autoimmunity in the C57BL/6 background (10).…”
Section: Resultsmentioning
confidence: 99%
“…Research is currently ongoing to characterize the cell-signaling mechanisms triggered by VISTA.COMP in both mouse and human T cells. Nonetheless, our data, combined with the observation of exacerbated autoimmune diseases upon genetic deletion of VISTA (15)(16)(17)(18), suggest a potential utility of targeting the VISTA-mediated immunosuppression pathway using a high-avidity VISTA-IgV containing scaffold to clinically suppress undesired immune responses.…”
Section: Discussionmentioning
confidence: 80%
“…increased levels of peripheral encephalitogenic T cells and develop an exacerbated form of experimental autoimmune encephalomyelitis (16). More recently, it was shown that VISTA-deficient mice exhibited worsened disease in a model of imiquimod-induced psoriasis, where enhanced TLR7 signaling in DCs led to augmented IL-23 production and increased expression of IL-17A in T cells (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation